ҚАРАҚАЛПАҚ ЛИРИКАЛЫҚ ПОЭМАСЫНЫҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИКЛЕРИ (Х.Дәўлетназаров ҳәм О.Сәтбаевлардың шығармалары мысалында) - Нуржанов, М. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of genre peculiarities of Karakalpak lyric poem of 1990 on the material of the books. Land with out a master by Kh. Dauletnazarov by O.Satbaev.
Keywords: Karakalpak poem; lyric poem; problems; comparative-typological analyses; lyric hero